A Ladder of Citizen Participation. Issue 1 (2nd January 2019) - Arnstein, Sherry R.
Abstract: The heated controversy over "citizen participation, " "citizen control, " and "maximum feasible involvement of the poor, " has been waged largely in terms of exacerbated rhetoric and misleading euphemisms. To encourage a more enlightened dialogue, a typology of citizen participation is offered using examples from three federal social programs: urban renewal, anti-poverty, and Model Cities. The typology, which is designed to be provocative, is arranged in a ladder pattern with each rung corresponding to the extent of citizens' power in determining the plan and/or program.